Caspase‐dependent cleavage regulates protein levels of Epstein–Barr virus‐derived latent membrane protein 1. Issue 6 (4th March 2016) - Togi, Sumihito; Hatano, Yosuke; Muromoto, Ryuta; Kawanishi, Eri; Ikeda, Osamu; Hirashima, Koki; Kon, Shigeyuki; Kitai, Yuichi; Yasui, Teruhito; Oritani, Kenji; Matsuda, Tadashi
Abstract : Epstein–Barr virus (EBV)‐encoded latent membrane protein‐1 (LMP1) plays pathogenic roles in EBV‐related diseases. Thus, host cells employ several mechanisms to regulate LMP1 functions, and we previously reported possible regulation by signal transducing adaptor protein‐2 as well as BS69. Here, we found that caspase‐3 mainly degraded LMP1 proteins in HeLa cells, leading to decreased NF‐κB and STAT3 activation. Caspase‐3 cleaved the consensus DNTD sequences in the CTAR3 region of LMP1. Of importance, LMP1 expression strongly enhanced caspase‐3 activity. Taken together, the reduction of LMP1 protein levels by caspases is likely to be a newly identified host defense against EBV infection. Abstract :